Long‐term ethanol effects on acute stress responses: modulation by dynorphin. (21st September 2012) - Rácz, Ildikó; Markert, Astrid; Mauer, Daniela; Stoffel‐Wagner, Birgit; Zimmer, Andreas
Abstract The brain stress‐response system is critically involved in the addiction process, stimulating drug consumption and the relapse to drug taking in abstinent addicts. At the same time, its functioning is affected by chronic drug exposure. Here, we have investigated the role of the endogenous opioid peptide dynorphin as a modulator of effects of long‐term ethanol consumption on the brain stress‐response system. Using the two‐bottle choice paradigm, we demonstrate an enhanced ethanol preference in male dynorphin knockout mice. Exposure to mild foot shock increased ethanol consumption in wild‐type control littermates, but not in dynorphin‐deficient animals. Blood adrenocorticotropic hormone levels determined 5 minutes after the shock were not affected by the genotype. We also determined the neuronal reactivity after foot shock exposure using c‐Fos immunoreactivity in limbic structures. This was strongly influenced by both genotype and chronic ethanol consumption. Long‐term alcohol exposure elevated the foot shock‐induced c‐Fos expression in the basolateral amygdala in wild‐type animals, but had the opposite effect in dynorphin‐deficient mice. An altered c‐Fos reactivity was also found in the periventricular nucleus, the thalamus and the hippocampus of dynorphin knockouts. Together these data suggest that dynorphin plays an important role in the modulation of the brain stress‐response systems after chronic ethanol exposure.